2012
DOI: 10.1093/hmg/dds059
|View full text |Cite
|
Sign up to set email alerts
|

High levels of somatic DNA diversity at the myotonic dystrophy type 1 locus are driven by ultra-frequent expansion and contraction mutations

Abstract: Several human genetic diseases are associated with inheriting an abnormally large unstable DNA simple sequence repeat. These sequences mutate, by changing the number of repeats, many times during the lifetime of those affected, with a bias towards expansion. These somatic changes lead not only to the presence of cells with different numbers of repeats in the same tissue, but also produce increasingly longer repeats, contributing towards the progressive nature of the symptoms. Modelling the progression of repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 57 publications
4
64
0
Order By: Relevance
“…As it is reasonable to expect these rates to be randomly distributed throughout the spectrum, the results indicate that the overall model may be improved by introducing a nonlinear response in line with the biological consideration that small alleles may have a reduced propensity to expand and/or contract owing to possible size effects [16].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…As it is reasonable to expect these rates to be randomly distributed throughout the spectrum, the results indicate that the overall model may be improved by introducing a nonlinear response in line with the biological consideration that small alleles may have a reduced propensity to expand and/or contract owing to possible size effects [16].…”
Section: Introductionmentioning
confidence: 86%
“…From these results, we concluded that mutations at the DM1 locus are ultra-frequent, much more frequent than might be concluded from the net gains or examination of the modal repeat length. In summary, both expansions and contractions have resulted in the characteristic shape of the repeat length distributions [16].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, as the DM1 CTG repeat is also highly unstable in the soma, [24][25][26][27][28] this approach frequently yields a diffuse smear for the expanded allele, from which it is only possible to estimate the modal allele length. 4,6,8,[10][11][12][13][14][15][16]20,29 As somatic mosaicism is expansion biased and age dependent, [24][25][26][27][28] the modal allele length thus measured also increases with age. 26 By performing multiple reactions with reduced amounts of input DNA, it is possible to use small pool PCR (SP-PCR) to resolve the diffuse smear into its component alleles 25 and estimate the progenitor allele length (PAL) transmitted from the affected parent.…”
Section: Introductionmentioning
confidence: 99%